Punishment for Cybercrime: A Major Challenge in Modern Legal Systems - Duha, Ridho (CV WAHANA PUBLIKASI, 2024)
Cybercrime represents a major challenge to modern legal systems due to its transnational nature and its continual evolution alongside digital technological advancements. The increasing intensity and complexity of cybercrime drives the need for an adaptive legal system that is able to provide effective legal protection. This study aims to analyze the application of penalties for cybercrime in Indonesia, assess its effectiveness, and compare it with legal practices at the international level. The approach used is normative juridical with qualitative analysis techniques on primary and secondary legal materials, including case studies of cybercrime in Indonesia, Singapore, and Estonia. The results of the study show that although Indonesia has a legal basis in the form of Law Number 11 of 2008 concerning Information and Electronic Transactions (ITE) and the Criminal Code, its implementation has not been optimal due to the weak technical capacity of the apparatus, minimal coordination across institutions, and the absence of a strong international cooperation mechanism. Comparative studies indicate that countries such as Singapore and Estonia have built a more proactive legal framework through a multi-level and integrative approach. The conclusion of this study emphasizes the importance of regulatory revision, increasing digital forensic capacity, and ongoing international cooperation. Practical implications of this study include the need to strengthen the law enforcement system, develop a national digital literacy policy, and greater involvement of the private sector in combating cybercrime.